A sport-oriented place branding strategy for cities, regions and countries. Issue 4 (10th August 2018) - Richelieu, Andre
Abstract : Purpose: How could a city, a region or a country succeed in its attempt to use sport to (re-)define, position and promote itself? Consequently, what do jurisdictions and brand managers need to consider when using sporting events as a leverage to market themselves abroad? The paper aims to discuss these issues. Design/methodology/approach: This paper draws from a combination of an extensive literature review and secondary data collection in order to build a conceptual framework, entitled the "diamond" of place branding through sport. Findings: Managers and politicians of cities, regions and countries should espouse a holistic approach when developing their place branding strategy through sport. This holistic approach can be articulated around four dimensions: sport, economic, commercial and social. Research limitations/implications: Drawing mainly from a literature review, with the support of concrete examples, this is a first step within the confines of an exploratory research. A future study could analyze the specific cases of jurisdictions and how these fit within the conceptual framework articulated in this paper. Originality/value: A place branding strategy through sport should be translated into a socio-economic legacy, with private and public benefits for the community. Ultimately, place branding through sport is one of the components of the overall place branding strategy of a jurisdiction.